1987
DOI: 10.1001/jama.1987.03390080057030
|View full text |Cite
|
Sign up to set email alerts
|

Therapy vs No Therapy for Bacteriuria in Elderly Ambulatory Nonhospitalized Women

Abstract: This prospective randomized study was undertaken to determine the efficacy of antimicrobial therapy compared with no therapy for bacteriuria in elderly ambulatory nonhospitalized women. Sixty-one women (mean age, 85.8 years) with bacteriuria were in the no therapy control group and 63 women (mean age, 85.8 years) with bacteriuria were in the therapy group; none had symptoms of urinary tract infection. One short course of antimicrobial therapy achieved a cure rate of 68.3% (43 of 63 women cured) two weeks after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

1987
1987
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 24 publications
2
36
0
3
Order By: Relevance
“…Based on recommendations of the Infectious Diseases Society of America, screening for or treatment of ASB are not recommended for the following persons: (1) diabetic women; (2) older persons living in the community or who are institutionalized; (3) persons who have spinal cord injury; and (4) catheterized patients while a catheter remains in situ [2]. Although a 3-day course of antibiotic therapy is shown to decrease the prevalence of bacteriuria at 6 months [10], no benefits in morbidity, mortality, and chronic urinary incontinence are demonstrated to date. The randomized trials leading to these recommendations are summarized in Table 1 [11][12][13][14].…”
Section: Management Of Asymptomatic Bacteriuriamentioning
confidence: 99%
“…Based on recommendations of the Infectious Diseases Society of America, screening for or treatment of ASB are not recommended for the following persons: (1) diabetic women; (2) older persons living in the community or who are institutionalized; (3) persons who have spinal cord injury; and (4) catheterized patients while a catheter remains in situ [2]. Although a 3-day course of antibiotic therapy is shown to decrease the prevalence of bacteriuria at 6 months [10], no benefits in morbidity, mortality, and chronic urinary incontinence are demonstrated to date. The randomized trials leading to these recommendations are summarized in Table 1 [11][12][13][14].…”
Section: Management Of Asymptomatic Bacteriuriamentioning
confidence: 99%
“…In these residents, the prevalence of bacteriuria correlates with the level of functional impairment. Prospective, randomized, comparative trials of treatment or no treatment of asymptomatic bacteriuria have consistently reported no benefits with antimicrobial treatment of bacteriuria in these populations [40][41][42][43]. Treatment of asymptomatic bacteriuria does not decrease symptomatic episodes or the prevalence of bacteriuria, and chronic genitourinary symptoms such as chronic incontinence are not improved.…”
Section: Elderly Residents Of Institutionsmentioning
confidence: 99%
“…46 Imaging should be obtained or considered if the patient has pyelonephritis and 47 Prospective, randomized trials consistently conclude that antimicrobial therapy for asymptomatic bacteriuria is not beneficial in most populations. [49][50][51][52][53][54][55] The main exception is in pregnant women, who benefit from treatment of asymptomatic bacteriuria.…”
Section: Imaging Studiesmentioning
confidence: 99%